Characterization of BaTi1-xZrxO3 thin films obtained by a soft chemical spin-coating technique - Pontes, F. M.; Escote, M. T.; Escudeiro, C. C.; Leite, E. R.; Longo, Elson [UNESP]; Chiquito, A. J.; Pizani, P. S.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2004)
Single-phase perovskite structure BaZrxTi1-xO3 (BZT) (0.05less than or equal toxless than or equal to0.25) thin films were deposited on Pt-Ti-SiO2-Si substrates by the spin-coating technique. The structural modifications in the thin films were studied using x-ray diffraction and micro-Raman scattering techniques. Lattice parameters calculated from x-ray data indicate an increase in lattice (a axis) with the increasing content of zirconium in these films. Such Zr substitution also result in variations of the phonon mode wave numbers, especially those of lower wave numbers, for BaZrxTi1-xO3 thin films, corroborate to the structural change caused by the zirconium doping. on the other hand, Raman modes persist above structural phase transition, although all optical modes should be Raman inactive in the cubic phase. The origin of these modes must be interpreted as a function of a local breakdown of the cubic symmetry, which could be a result of some kind of disorder. The BZT thin films exhibited a satisfactory dielectric constant close to 181-138, and low dielectric loss tan delta<0.03 at the frequency of 1 kHz. The leakage current density of the BZT thin films was studied at elevated temperatures and the data obey the Schottky emission model. Through this analysis the Schottky barrier height values 0.68, 1.39, and 1.24 eV were estimated to the BZT5, BZT15, and BZT25 thin films, respectively. (C) 2004 American Institute of Physics.